Secure user authentication scheme for wireless healthcare sensor networks. (April 2017) - Liu, Chia-Hui; Chung, Yu-Fang
Abstract: Recently, countries worldwide have actively developed approaches to improve the quality of healthcare and reduce healthcare costs. One of these approaches involves replacing human labor with wireless information transmission. On the basis of the wireless sensor networks employed for medical monitoring in hospitals and healthcare institutions, this paper proposes a user authentication scheme and data transmission mechanism that facilitates security and privacy protection, enable medical personnel to instantly monitor the health conditions of care receivers, and provide care receivers with prompt and comprehensive medical care. Using both smart cards and passwords, our scheme grants only legal medical personnel access to patient information such as body temperature, heart rate, and blood pressure. In addition, a secure cryptosystem was applied for establishing a data transmission mechanism. Furthermore, this scheme can resist common attacks, such as impersonation, replay, online or offline password guessing, and stolen-verifier attacks.